The Influence of the International Oil Price on the EUR/USD Exchange Rate - Dias, Rui; Galvão, Rosa; Alexandre, Paulo; Teixeira, Nuno; Palma, Cristina; Leote, Francisco (Journal of Ecohumanism, 2025)
The study analyses the influence of the international oil price, focusing on the CBOE Crude Oil Volatility Index and Brent crude oil, on the main exchange rates: EUR/GBP, EUR/USD, GBP/USD, USD/CHF and USD/JPY. The analysis covers the period from 3 January 2022 to 8 December 2024 to examine the relationship between fluctuations in the oil market and the behaviour of exchange rates. The results show that the CBOE index directly impacts the EUR/GBP currency pair, reflecting the influence of global volatility on financial markets. The EUR/USD pair is influenced by the behaviour of the USD/JPY currency pair, showing the interconnection between the major currencies. Brent futures significantly affect the USD/CHF and USD/JPY currency pairs due to the importance of oil as a strategic commodity and the sensitivity of currencies such as the Yen and Swiss franc to fluctuations in energy prices. These relationships show the strong interconnectedness of global markets, highlighting the importance of informed risk management and decision-making strategies in interdependent environments.